2022
DOI: 10.3390/nu14173459
|View full text |Cite
|
Sign up to set email alerts
|

Berberine in Non-Alcoholic Fatty Liver Disease—A Review

Abstract: The incidence of Non-Alcoholic Fatty Liver Disease (NAFLD) has been rapidly increasing during the last decade. It is a relevant health problem that affects 25% of the general population. NAFLD involves an extensive array of clinical conditions. So far, no approved pharmacological therapy for NAFLD has been developed. Multiple bioactive compounds have been proposed to treat NAFLD. One of the most promising is Berberine (BBR). Its pleiotropic effect positively impacts various cardiometabolic aspects. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Glycyrrhetinic acid, another active ingredient of licorice, can also improve the damaged autophagy flux and reduce the excessive production of inflammatory cytokines such as TNF-α, IL-6 and IL-1β by regulating the STAT3-HIF-1 pathway of macrophages ( 200 ). Curcumin and berberine, two of the most studied natural products for the treatment of NAFLD, have shown positive results in several clinical trials ( 201 , 202 ). Mechanistic studies have also demonstrated the effect of both on macrophage polarization ( 203 , 204 ).…”
Section: Potential Drugs Targeting Pcd Of Macrophagesmentioning
confidence: 99%
“…Glycyrrhetinic acid, another active ingredient of licorice, can also improve the damaged autophagy flux and reduce the excessive production of inflammatory cytokines such as TNF-α, IL-6 and IL-1β by regulating the STAT3-HIF-1 pathway of macrophages ( 200 ). Curcumin and berberine, two of the most studied natural products for the treatment of NAFLD, have shown positive results in several clinical trials ( 201 , 202 ). Mechanistic studies have also demonstrated the effect of both on macrophage polarization ( 203 , 204 ).…”
Section: Potential Drugs Targeting Pcd Of Macrophagesmentioning
confidence: 99%
“…Berberine can directly or indirectly target multiple pathways involved in the brotic reactions in HSCs 24 . Therefore, it has received considerable attention in the treatment of MASH 25 . Herein, we used different concentrations of TJ-15 to observe its effects on LX2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical studies show that berberine has glucose-and lipid-lowering effects, which may be beneficial for patients with NAFLD/NASH. 76 In an RCT involving 184 patients with NAFLD, treatment with berberine plus lifestyle intervention reduced LFC more significantly than lifestyle intervention alone. This was accompanied by better improvement in body weight, homeostasis model assessment of insulin resistance (HOMA-IR) index, and serum lipid profile.…”
Section: A Phase II Trial Investigating the Efficacy And Safety Of Ch...mentioning
confidence: 99%
“…Berberine, an active single compound extracted from the Chinese herb Coptis chinensis , is widely used in China to treat diarrhoea. Preclinical and clinical studies show that berberine has glucose‐ and lipid‐lowering effects, which may be beneficial for patients with NAFLD/NASH 76 . In an RCT involving 184 patients with NAFLD, treatment with berberine plus lifestyle intervention reduced LFC more significantly than lifestyle intervention alone.…”
Section: Advances In Nafld/nash Treatment Regimens In Chinamentioning
confidence: 99%